Acoustic vibrations contribute to the diffuse scatter produced by ribosome crystals - Polikanov, Yury S. (Acta Crystallogr D Biol Crystallogr, 2015)
The diffuse scattering pattern produced by frozen crystals of the 70S ribosome from Thermus thermophilus is as highly structured as it would be if it resulted entirely from domain-scale motions within these particles. However, the qualitative properties of the scattering pattern suggest that acoustic displacements of the crystal lattice make a major contribution to it.